Diverse Rotations and Optimal Cultural Practices Control Wild Oat (Avena fatua). Issue 1 (March 2016) - Harker, K. Neil; O'Donovan, John T.; Turkington, T. Kelly; Blackshaw, Robert E.; Lupwayi, Newton Z.; Smith, Elwin G.; Johnson, Eric N.; Pageau, Denis; Shirtliffe, Steven J.; Gulden, Robert H.; Rowsell, John; Hall, Linda M.; et al.
Abstract : In western Canada, more money is spent on wild oat herbicides than on any other weed species, and wild oat resistance to herbicides is the most widespread resistance issue. A direct-seeded field experiment was conducted from 2010 to 2014 at eight Canadian sites to determine crop life cycle, crop species, crop seeding rate, crop usage, and herbicide rate combination effects on wild oat management and canola yield. Combining 2× seeding rates of early-cut barley silage with 2× seeding rates of winter cereals and excluding wild oat herbicides for 3 of 5 yr (2011 to 2013) often led to similar wild oat density, aboveground wild oat biomass, wild oat seed density in the soil, and canola yield as a repeated canola–wheat rotation under a full wild oat herbicide rate regime. Wild oat was similarly well managed after 3 yr of perennial alfalfa without wild oat herbicides. Forgoing wild oat herbicides in only 2 of 5 yr from exclusively summer annual crop rotations resulted in higher wild oat density, biomass, and seed banks. Management systems that effectively combine diverse and optimal cultural practices against weeds, and limit herbicide use, reduce selection pressure for weed resistance to herbicides and prolong the utility of threatened herbicide tools.